To solve for x, we need to isolate x on one side of the equation.
9x + 16 = 6x + 1
First, we want to get the x terms on one side of the equation by subtracting 6x from both sides:
9x - 6x + 16 = 6x - 6x + 1
This simplifies to:
3x + 16 = 1
Next, we want to get rid of the constant term on the side with x by subtracting 16 from both sides:
3x + 16 - 16 = 1 - 16
This simplifies to:
3x = -15
Lastly, we divide by 3 to solve for x:
3x/3 = -15/3
x = -5
Therefore, the solution to the equation 9x + 16 = 6x + 1 is x = -5.
solve for x: 9x + 16 = 6x + 1
1 answer